Analysis of Chemical Castration Sanctions in the Positive Legal System in Indonesia - HR. Nurfaiz Mohamad; Lisnawaty W. Badu; Avelia Rahma Y. Mantali (SEAN Institute, 2025)
This study analyzes the application of chemical castration as a form of punishment for perpetrators of sexual crimes against children in Indonesia's positive legal system, as well as its relation to human rights principles. Chemical castration is regulated in Government Regulation No. 70 of 2020 as an additional punishment to suppress the sexual urges of perpetrators, but it has sparked controversy regarding violations of the right to bodily integrity and the potential for cruelty that is contrary to the constitution and international conventions. This study uses a normative legal research method with a descriptive qualitative approach to examine regulations, court decisions, and the views of various parties such as Komnas HAM, IDI, and international human rights institutions. The results of the study show that chemical castration has not been proven effective in preventing repeat offenses and focuses more on the theory of revenge than rehabilitation. In addition, there are more humane alternatives, such as a therapy program in Germany that emphasizes a rehabilitative approach and the protection of the rights of both perpetrators and victims. This study recommends a review of the chemical castration policy policy to bring it in line with the values of justice, humanity, and the supremacy of human rights in Indonesia.